2022
DOI: 10.1002/ajmg.c.32003
|View full text |Cite
|
Sign up to set email alerts
|

Georgia state spinal muscular atrophy newborn screening experience: Screening assay performance and early clinical outcomes

Abstract: The purpose of this study is to provide the results of the newborn screening (NBS) program for Spinal Muscular Atrophy (SMA) in the state of Georgia to determine disease incidence, time to diagnosis and treatment, and early outcomes. NBS for SMA was performed using real time PCR assays from February 2019 through February 2020 in a pilot phase of screening. This method continued as part of our official state panel, and here we describe the pilot period as well as the first year of standard screening through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 19 publications
(48 reference statements)
0
25
0
Order By: Relevance
“…Given the enormous psychological impact of a false positive result on the family, care must be taken to ensure that the number of false positives approaches zero [12,19]. Figures such as 61% of suspicious results which could not be confirmed in a pilot project are definitely too high [20]. To improve the quality of NBS, both preanalytical and analytical problems need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Given the enormous psychological impact of a false positive result on the family, care must be taken to ensure that the number of false positives approaches zero [12,19]. Figures such as 61% of suspicious results which could not be confirmed in a pilot project are definitely too high [20]. To improve the quality of NBS, both preanalytical and analytical problems need to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Real-world studies conducted in various countries, particularly those linked to expanded newborn screening (NBS) programs, have consistently shown that early initiation of gene replacement therapy in pre-symptomatic infants with SMA-5q results in remarkable developmental progress, with children achieving motor milestones within the expected developmental timeframe. 108 113 114 115 Furthermore, cost-effectiveness studies, particularly in countries like Australia, have shown that implementing neonatal screening for SMA-5q, coupled with early gene replacement therapy treatment, leads to reduced costs or remains within the cost-effectiveness threshold considered by these countries in the long term. 116 …”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons for the minimal effect of VE alone on the pro-inflammatory effect may be related to less toxic chemicals contained in VE as compared to tobacco (regular) cigarettes. [42][43][44] There are several limitations to our study. First, we only included one human donor in this pilot study, requiring validation in future experiments.…”
Section: Discussionmentioning
confidence: 97%
“…One of the reasons for the minimal effect of VE alone on the pro-inflammatory effect may be related to less toxic chemicals contained in VE as compared to tobacco (regular) cigarettes. 42 44 …”
Section: Discussionmentioning
confidence: 99%